2022
DOI: 10.1093/jbcr/irac055
|View full text |Cite
|
Sign up to set email alerts
|

Parent Traumatic Stress After Minor Pediatric Burn Injury

Abstract: Parents are at increased risk for psychological sequelae following their child’s burn injury which has demonstrated negative impacts on the child. The current study sought to address gaps in the literature on risk factors for parental distress by examining the relationships among demographic variables, burn characteristics, and child functioning after burn injury, with parent post-traumatic stress symptoms (PTSS). Participants included parents of 660 pediatric burn patients from a regional burn clinic. Parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…One study in the Netherlands found that parents of pediatric burn survivors are prone to developing post-traumatic stress disorder (PTSD), which can adversely affect the psychological health of the child (19-20). Moreover, a pilot study highlighted the substantial financial impact of pediatric burns on families, particularly when the injuries involve flames or a larger TBSA (21)(22). Despite the significant challenges faced by parents of pediatric burn patients, the literature reveals a lack of focused research on their experiences, particularly in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…One study in the Netherlands found that parents of pediatric burn survivors are prone to developing post-traumatic stress disorder (PTSD), which can adversely affect the psychological health of the child (19-20). Moreover, a pilot study highlighted the substantial financial impact of pediatric burns on families, particularly when the injuries involve flames or a larger TBSA (21)(22). Despite the significant challenges faced by parents of pediatric burn patients, the literature reveals a lack of focused research on their experiences, particularly in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Parents, carers and extended family of children who sustain a burn injury experience significant stress from witnessing a potentially life-changing injury, guilt in relation to responsibility for the injury and trauma through participating in their child’s painful medical procedures and worrying about the impact of the burn on the child’s future. 5–8 Parents of children with burn injuries experience higher psychological distress than parents of children with other types of injuries and medical conditions. 9 Parents of children hospitalised for burns injuries experience anxiety, depression and post-traumatic stress disorder (PTSD) for up to 7 years after the injury.…”
Section: Introductionmentioning
confidence: 99%